Production and marketing practices of rabbit raisers in Bulacan, Philippines - Dionisio, Kathleen T.; Banes, Charlene A.; Nicolas, Honeylet J.; Santos, Susan C. (Annals of Tropical Research, 2023)
The rabbit is a promising livestock animal as it has nutritious meat, can adapt to a variety of climates and has prolificacy. However, it is not as well-studied in the Philippines as other livestock or poultry species, particularly regarding the status of farmers in the country. This study is a baseline study on rabbit raisers in the Philippines, which can help promote a better understanding of this industry. This study, conducted in the Province of Bulacan, employed a descriptive research design using a validated survey questionnaire and convenience sampling technique. Among 91 farmers surveyed, most were 41-50 years old, male, married, and college graduates. The majority had small-scale farms, with the New Zealand rabbit as the most common breed. Feeding was done mainly by giving forage and commercial pellets. Housing was located outdoors, usually in double tier cages made of wire mesh, equipped with feeders, automatic waterers, and plastic nest boxes. Raisers used natural farming systems and avoided the use of commercial medications. The majority had less than one year of farm expedience. The most common products were meat, manure, and fur. The challenges encountered were inadequate capital, the high cost of feed, and negative perceptions about rabbit meat. The rabbit raisers were most interested in training on diseases, marketing, breeding, and processing. Rabbit raisers need technical support for the production and marketing of rabbits from the Philippine Government and other institutions to develop more successful rabbit raising enterprises.